2012
DOI: 10.1080/07315724.2012.10720427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baked Products Enriched with n-3 Fatty Acids, Folates, β-glucans, and Tocopherol in Patients with Mild Mixed Hyperlipidemia

Abstract: Baked functional products enriched with n-3 fatty acids, folates, β-glucans, and tocopherols within the context of a balanced diet lower fasting and postprandial plasma triglycerides, fasting homocysteinemia, and the postprandial insulin peak. They induce a greater feeling of satiety with possible beneficial implications on energy intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It has been repeatedly demonstrated that reducing the viscosity of DF following acid hydrolysis results in concurrent loss of its clinical efficacy ( Riccardi et al., 2004 ). Several types of soluble fibre, including β-glucan, psyllium and guar gum, reduce postprandial glucose and insulin responses, and improve insulin sensitivity both in diabetic and non-diabetic individuals ( De Natale et al., 2012 ; Riccardi et al., 2005 ).…”
Section: Contributions Of Grain Carbohydrates To Diet and Healthmentioning
confidence: 99%
“…It has been repeatedly demonstrated that reducing the viscosity of DF following acid hydrolysis results in concurrent loss of its clinical efficacy ( Riccardi et al., 2004 ). Several types of soluble fibre, including β-glucan, psyllium and guar gum, reduce postprandial glucose and insulin responses, and improve insulin sensitivity both in diabetic and non-diabetic individuals ( De Natale et al., 2012 ; Riccardi et al., 2005 ).…”
Section: Contributions Of Grain Carbohydrates To Diet and Healthmentioning
confidence: 99%
“…Glucans are the major structural components of the cell wall of fungi, grass and some bacteria [20]. Among the glucans, beta-glucans (BG) have been highlighted as prebiotics used as modulators both of the immune response [21], as well as lipid and carbohydrate metabolism [5].…”
Section: Prebioticsmentioning
confidence: 99%
“…Among the main classes of prebiotics are galacto-oligosaccharides (GOS), fructooligosaccharides (FOS), insulin and beta-glucans (BG) [4]. BG's have been widely investigated due to their immunomodulatory activity [4], as well as to the activity on the metabolism of carbohydrates and lipids [5]. In this sense, we aimed to present the functional effects of BGs on the immune response and metabolism.…”
Section: Introductionmentioning
confidence: 99%